2008
DOI: 10.1002/glia.20662
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia and downregulation of caveolin‐1 enhance neuregulin‐induced demyelination

Abstract: Neuregulins (NRGs) are growth factors which bind to Erb receptor tyrosine kinases that localize to Schwann cells (SCs). Although NRGs can promote cell survival, mitogenesis, and myelination in undifferentiated SCs, they also induce demyelination of myelinated co-cultures of SCs and dorsal root ganglion (DRG) neurons. We have shown previously that Erb B2 activity increased in premyelinating SCs in response to hyperglycemia, and that this correlated with the downregulation of the protein caveolin-1 (Cav-1). As m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 45 publications
1
49
0
Order By: Relevance
“…Caveolin-1 is a structural protein found in specialized sphingolipid-cholesterol microdomains called caveolae, which are thought to be important for Schwann cell physiology because cholesterol comprises ~25% of the total lipid content of myelin 142 . In this study, the reduction of caveolin-1 prolonged the kinetics of ErbB2 phosphorylation and enhanced the mitogenic response of Schwann cells to neuregulin1-β1; sub sequent studies have demonstrated that changes in caveolin-1 expression in Schwann cells co-cultured with neurons leads to neuregulin-induced demyelination, and that interactions between caveolin-1 and ErbB2 signalling contribute to peripheral neuropathy in rodents with diabetes 143,144 .…”
Section: Impact Of Schwannopathy On Neuronsmentioning
confidence: 56%
See 1 more Smart Citation
“…Caveolin-1 is a structural protein found in specialized sphingolipid-cholesterol microdomains called caveolae, which are thought to be important for Schwann cell physiology because cholesterol comprises ~25% of the total lipid content of myelin 142 . In this study, the reduction of caveolin-1 prolonged the kinetics of ErbB2 phosphorylation and enhanced the mitogenic response of Schwann cells to neuregulin1-β1; sub sequent studies have demonstrated that changes in caveolin-1 expression in Schwann cells co-cultured with neurons leads to neuregulin-induced demyelination, and that interactions between caveolin-1 and ErbB2 signalling contribute to peripheral neuropathy in rodents with diabetes 143,144 .…”
Section: Impact Of Schwannopathy On Neuronsmentioning
confidence: 56%
“…The remaining cells look thin and short, and fail to adequately extend processes 75,147 , and chromatin becomes increasingly condensed with shrinkage of the Schwann cell cytosol 158,159 . When co-cultured with neurons, hyperglycaemiastressed Schwann cells are dysfunctional 143 , and a study from 2014 suggests that the stress causes them to produce VEGF, which subsequently impairs neurite outgrowth from co-cultured sensory neurons 160 . These observations indicate that impaired nerve regeneration after injury in diabetes is, at least in part, secondary to disruption of Schwann cell metabolism.…”
Section: Impact Of Schwannopathy On Neuronsmentioning
confidence: 99%
“…Because thermal sensitivity is mediated primarily via unmyelinated C fibers (Julius and Basbaum, 2001), these data indicate that myelinated fibers may be more sensitive to pathological activation of Erb B2. In this regard, hyperglycemia increased the extent of neuregulin-induced demyelination in myelinated Schwann cell-sensory neuron cocultures (Yu et al, 2008). However, the effect of diabetes on the expression of various neuregulin-1 isoforms and whether they contribute to myelin thinning in peripheral nerve remains to be determined.…”
Section: H Growth Factorsmentioning
confidence: 99%
“…Is cav-1, which regulates cholesterol trafficking and homeostasis, involved in periods of high cholesterol requirement such as myelination and regeneration? Can down-regulation of cav-1 sensitize myelinated axons of the CNS to degenerative conditions, as shown for demyelination in the PNS (Yu et al, 2008)? Overall, it seems worthwhile to place more attention on the potential effects of caveolin expression on oligodendroglial differentiation/myelination and regeneration.…”
Section: Ngf Increases Tyrosine Phosphorylation Of Cav-1mentioning
confidence: 99%